Es kommt weniger darauf an, mehr zu geben, als weniger zu nehmen
Finanzwesen;Geld- und Kreditwesen;Bankgeschäft;Bankgeheimnis politischer Rahmen;Wahlen und Abstimmungen;Volksabstimmung;Volksinitiative